FX Intervention to Stabilize or Manipulate the Exchange Rate? : Inference from Profitability - Sandri, Damiano (IMF Working Papers; Working Paper ;, 2020)
We analyze the profitability of FX swaps used by the central bank of Brazil to shed light on the rationale for FX intervention. We find that swaps are profitable in expectation, suggesting that FX intervention is used to stabilize the exchange rate in the face of temporary excessive movements rather than to manipulate it away from fundamental values. In line with this interpretation, we find that the scale of FX intervention responds to the degree of exchange rate misalignment relative to UIP conditions. We also document that intervention is more aggressive when there is less uncertainty about the medium-term level of the exchange rate and when the exchange rate is overvalued rather than undervalued.